The Role of the Fun Day Friday Creativity Program in Increasing Children's Interest in Learning in Rantau Panjang Village - Ginting, Rehulina Zuhra; Ananda, Dhio Rizky; Pane, Yuni Kartika; Harahap, Raihan Rizieq; Ahmad, Zidratul Gemilang (Jurnal Abdi Mas Adzkia, 2023)
Every child needs to have and develop creativity. In this study, researchers (the group of KKN 70 UIN SU Rantau Panjang Village) created a creativity program called Fun Day Friday. This program was initiated due to the need for more creativity and interest in learning among children in Rantau Panjang Village. Thus, this Fun Day Friday program aims to improve the value of creativity and interest in learning for children in Rantau Panjang Village. This study used a qualitative method with a Participatory Action Research (PAR) approach, in which students of SDN 101928 Rantau Panjang became participants in this study. After the program has been carried out, there are positive results for the children in Rantau Panjang Village. This can be seen from their improved interest in learning in the classroom, such as being constantly present throughout the lesson, responding actively to questions, and the classroom atmosphere becoming more conducive.Keywords: Children, Creativity, Fun Day Friday, Learning Interest